FLASH Radiotherapy With Electrons: Issues Related to the Production, Monitoring, and Dosimetric Characterization of the Beam - Di Martino, Fabio; Barca, Patrizio; Barone, Salvatore; Bortoli, Eleonora; Borgheresi, Rita; De Stefano, Silvia; Di Francesco, Massimo; Faillace, Luigi; Giuliano, Lucia; Grasso, Luigi; Linsalata, Stefania; Marfisi, Daniela; et al. (Frontiers in Physics, 2020)
Various in vivo experimental works carried out on different animals and organs have shown that it is possible to reduce the damage caused to healthy tissue still preserving the therapeutic efficacy on the tumor tissue, by drastically reducing the total time of dose delivery (<200 ms). This effect, called the FLASH effect, immediately attracted considerable attention within the radiotherapy community, due to the possibility of widening the therapeutic window and treating effectively tumors which appear radioresistant to conventional techniques. Despite the experimental evidence, the radiobiological mechanisms underlying the FLASH effect and the beam parameters contributing to its optimization are not yet fully known. In order to fully understand the FLASH effect, it might be worthy to investigate some alternatives which can further improve the tools adopted so far, both in terms of linac technology and dosimetric systems. This work investigates the problems and solutions concerning the realization of an electron accelerator dedicated to FLASH and optimized for in vivo experiments. Moreover, the work discusses the saturation problems of the most common radiotherapy dosimeters when used in the very high dose-per-pulse FLASH region and provides some preliminary experimental data on their behaviour.